Del Nido cardioplegia better preserves cardiac diastolic function but histidine–tryptophan–ketoglutarate is better for endothelial function. (26th January 2022) - Xue, Hong-Mei; Hou, Hai-Tao; Sun, Wen-Tao; Wang, Shi-Fu; Guo, Shan; Yang, Qin; He, Guo-Wei
Abstract: OBJECTIVES: The effectiveness of myocardial protection of cardioplegia has been a matter of debate for decades. This study was designed to compare cardiac and endothelial protection of 3 clinically used cardioplegias: del Nido cardioplegia (DNC), histidine–tryptophan–ketoglutarate (HTK) and blood cardioplegia (BC) followed by HTK (BC + HTK) in a rat model of ischaemia/reperfusion (I/R). METHODS: Sixty male Wistar rats were subjected to either 120 min of global ischaemia at 4°C followed by 90 min of reperfusion (I/R) at 37°C or no I/R (control) in a Langendorff apparatus and were randomly allocated to 5 groups: control, I/R, DNC, HTK and BC + HTK. Cold cardioplegia solutions were administered at doses of 20 ml/kg for DNC and HTK or 10 ml/kg for BC followed by HTK. Haemodynamic parameters were continuously recorded using an intraventricular balloon. The endothelium-dependent relaxation to acetylcholine was measured in the left anterior descending artery using a myograph. Protein expression of cardiac troponin T (cTnT) and creatine kinase MB was determined by western blot. RESULTS: During reperfusion, HTK had higher left ventricular systolic pressure whereas DNC had lower left ventricular end-diastolic pressure, better left ventricular developed pressure and best +d p /d t max and −d p /d t max than the other 2 groups but the differences disappeared at the end of the reperfusion. HTK or BC + HTK preserves the acetylcholine-induced endothelium-dependent relaxation better than DNC ( E max = 48.2 ± 8.0% in DNC vs 75.0 ± 8.0% in HTK, P < 0.05; vs 96.9 ± 3.5% in BC + HTK, P < 0.001). The protein levels of cTnT and creatine kinase MB were downregulated in the 3 groups. CONCLUSIONS: All 3 cardioplegias prevented myocardial damage against I/R injury at the end of reperfusion. DNC demonstrated better preserved diastolic function of the left ventricle whereas HTK or BC + HTK showed better preserved coronary endothelial function. These findings may suggest that currently no 'perfect' cardioplegia exists and that exploration for the 'perfect' cardioplegia is needed. Abstract : Ischaemia/reperfusion (I/R) injury, which might lead to postoperative myocardial dysfunction, is inevitable during cardiac surgery.